Improvement in CBR Value of Sub-Base Soil using Concrete Slush Waste (CSW) - Akbar, Noor Azlina; Tuan Ismail, Tuan Noor Hasanah; Adnan, Suraya Hani; Mohamed Yusop, Fatimah; Khosran, Hafizah; Saji, Nurdalila (Journal of Advanced Industrial Technology and Application, 2020)
The earthen material and its properties are essential in the design of the pavement system as they affect the pavement’s strength and stability, even under adverse traffic and environmental conditions. Unfortunately, earthen on-site has not always had a suitable property to be used as a good quality material for road pavement construction. Thus, soil efficiency should be enhanced by modification and stabilisation techniques to sustain structure without failure thereon. The present study was performed to evaluate the appropriateness and effectiveness of concrete slush waste (CSW) as a by-product construction material obtained from a concrete batching plant at Durable Mix, Panchor, Muar, Johor, and it was investigated as an additive material for road sub-base. This study aimed to improve the strength performance of locally available soil around Pagoh, Muar, Johor, Malaysia. The general properties tests include hydrometer, Atterberg limit, and a specific gravity test that were conducted to identify and classify the type of soil used throughout this study. Subsequently, standard compaction and California bearing ratio tests were performed to study the effect of CSW on the geotechnical properties of stabilised-soil. Based on the index properties results, the soil sample used is graded as high plasticity clay soil, consisting of liquid limit (LL) more than 50%, plastic limit (PI) more than 30 %, a specific gravity of 2.56, and 45.2% fines particles passing through sieve No. 200. The compaction results showed that the maximum dry density (MDD) decrease and optimum moisture content (OMC) value increased when mixed with CSW. The results show that the CBR value significantly increases from 9.70% to 45.44%, with the rise in CSW percentages from 0% to 12%, and it was achieved the highest value at 1.2% of CSW content. The findings show that the CWS has been proven as a potential material in enhanced soil efficiency, which meets the necessary strength recommended by the Malaysian Public Works Department (JKR) for road sub-base. Besides that, by utilisation of CSW in the soil would also encourage sustainable and cost-effectiveness practice in road construction.